CHOLESTEATOMA OF THE PETROSAL APEX: A RARE TUMOR - Pykocz, Adrielle Holler (2024)
Introduction: Cholesteatoma, although relatively rare, presents significant challenges in clinical practice. Despite decades of research, its cause remains complex and elusive. Objective: This review aimed to summarize key findings on the epidemiology, pathophysiology, diagnosis and surgical management of cholesteatoma, highlighting current knowledge gaps and emerging trends in the field. Method: Narrative review carried out in the PubMed and Scielo databases. The search used the following keywords: “cholesteatoma, petros apex, minimally invasive surgical procedures”. The inclusion criteria comprised review articles, pre-clinical and clinical research published, written in Portuguese and English and available in complete text. The selected articles were analyzed based on the technologies covered, future perspectives, challenges, diseases mentioned and the central idea of the article. Result: 36 articles were included. Conclusion: Cholesteatoma is important in medical practice, despite being relatively uncommon in the general population. However, there are still doubts about its cause, but its diagnosis has been expanded through imaging tests in an attempt to reduce “second-look” operations and avoid them. Another field with constant growth is surgical treatment, since the complex anatomy requires that new techniques be managed to reduce injuries to important and vital structures in the region.